FORMATION OF A SPIRITUAL WORLDVIEW OF PRESCHOOL CHILDREN THROUGH THE MEANS OF GENRES OF FOLK ORAL CREATIVITY - Azizova Ziroat Baxodirovna; Azizova Xonzodabegim Akmal qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article focuses on aspects of the formation of pedagogical and psychological competence in future pedagogues. The scientific theoretical importance of the issue of preparing students for folk art in the spirit of love, its level of study and its importance at the present time are highlighted.